Bengal stream : the vibrant architecture scene of Bangladesh - Graber,Niklaus; Ruby, Andreas; Ehrensberger, Viviane; Baan, Iwan (Christoph Merian Verlag, 2017)
Dhaka, the capital of Bangladesh, has one of the most important buildings of the 20th century: its parliamentary building by Louis I. Kahn constructed between 1961 and 1982. Little is known, however, about the local architecture scene that has emerged since then. Yet contemporary architecture in Bangladesh exhibits a strong formal idiom that has its roots in tradition and is combined with an innovative handling of local resources such as bamboo and brick.00Exhibition: S AM Schweizerisches Architekturmuseum, Basel, Switzerland (02.12.2017 - 06.05.2018).